Community structure of sea cucumber (Echinodermata: Holothuroidea) resources in the Kepulauan Seribu National Park, Indonesia - NAZWA AYUNDA HELMIYANI; SURYANTI SURYANTI; FRIDA PURWANTI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Helmiyani NA, Suryanti S, Purwanti F. 2024. Community structure of sea cucumber (Echinodermata: Holothuroidea) resources in the Kepulauan Seribu National Park, Indonesia. Biodiversitas 25: 344-354. Kepulauan Seribu National Park has several types of commercial sea cucumbers (Echinodermata: Holothuroidea). Many local and foreign communities take sea cucumbers from nature without paying attention to habitat conditions. This phenomenon causes a decrease in the availability of sea cucumbers. This research was carried out to help stabilize the sea cucumber ecosystem and its availability to be considered for its sustainability. This research was conducted in May-June 2023, at Kelapa Dua Island and Panjang Kecil Island in the Kepulauan Seribu National Park, Jakarta, Indonesia. Sampling was carried out using the field observation method, where the location points were determined by adjusting where the sea cucumber habitat was located. Sampling points were carried out on two islands, each island was assigned 4 station points, with the total number of stations on both islands being 8 station points. Sampling was carried out using perpendicular transect lines, divided into 3 zones. The data analyzed includes the Index of Diversity, Evenness, Dominance and Density. Based on the results 12 species were obtained from both islands, with the genera Holothuria, Stichopus, Bohadschia, Actinopyga, and Synapta. The highest density is at station 3 Kelapa Dua Island, with a density value of 0.57 (ind/m2), and the lowest density is at station 1 Panjang Kecil Island with a value of 0.14 (ind/m2). The results show a moderate diversity value, a low Dominance value, and a small evenness value, while the water quality result value can be said to be good because it has a value according to the survival quality standards for sea cucumbers in marine waters.